2012
DOI: 10.1111/j.1369-1600.2011.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Operant model of frustrated expected reward in mice

Abstract: One aspect of the addictive process that has not been thoroughly investigated is the consequence of the frustrated state occurring when the drug is not available. The present study aimed to validate a novel operant model of frustrated expected reward in mice.C57BL/6J mice were trained in operant conditioning maintained by chocolate-flavoured pellets or cocaine. After the completion of high rates of responding on a progressive ratio schedule, the reward was unexpectedly withheld. The consequences of this frustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…Nociception (1), physical dependence and withdrawal (1, 26), locomotor activity (20), locomotor sensitization (27), bar test (28), conditioned place preference (CPP) (29) and SA procedures (20, 30, 31) are described in Supplemental Information.…”
Section: Methodsmentioning
confidence: 99%
“…Nociception (1), physical dependence and withdrawal (1, 26), locomotor activity (20), locomotor sensitization (27), bar test (28), conditioned place preference (CPP) (29) and SA procedures (20, 30, 31) are described in Supplemental Information.…”
Section: Methodsmentioning
confidence: 99%
“…In an extension of Amsel’s work, one study demonstrated an interaction between FNR and threat processing, in that frustrated mice exhibited increased aggressive responses in an intruder paradigm ([12], Figure 1). Indeed, based on other rodent research, Gray [13] proposed the “fear=frustration” hypothesis, suggesting that frustration is processed as a threat and responses to both are mediated by the behavioral inhibition system.…”
Section: The Neuroscience Of Irritabilitymentioning
confidence: 99%
“…Top left: When exposed to the threat of a conspecific in a resident intruder paradigm, frustrated mice show increased aggressive behavior. This aggression is greater than that exhibited by non-frustrated mice (not shown) [12]. Bottom left: Irritability in youth is associated with aberrant amygdala-prefrontal cortex connectivity when viewing threatening faces [37]; see Figure 2 for details.…”
Section: Figure 1 (Key Figure)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine self-administration sessions were performed in accordance to protocols previously described (Burokas et al, 2012;Martin-Garcia et al, 2009;Soria et al, 2008;Soria et al, 2005). Details of the apparatus, surgery, and the nicotine self-administration procedure are included in the Supplementary Information.…”
Section: Intravenous Nicotine Self-administrationmentioning
confidence: 99%